Godwill Address by Executive Director of CORAF - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Workshop on the Sahel Region: Godwill Address by Executive Director of CORAF, Dr. Abdou Tenkouano. Workshop on Partnerships to address the challenges of agriculture in the Sahel